2020
DOI: 10.3390/catal10080828
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mg Contents on Catalytic Activity and Coke Formation of Mesoporous Ni/Mg-Aluminate Spinel Catalyst for Steam Methane Reforming

Abstract: Ni catalysts are most suitable for a steam methane reforming (SMR) reaction considering the activity and the cost, although coke formation remains the main problem. Here, Ni-based spinel catalysts with various Mg contents were developed through the synthesis of mesoporous Mg-aluminate supports by evaporation-induced self-assembly followed by Ni loading via incipient wetness impregnation. The mesoporous Ni/Mg-aluminate spinel catalysts showed high coke resistance under accelerated reaction conditions (0.0014 gc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…There are various common strategies to improve catalyst stability, such as reducing the acidic sites of the support [26], enhancing metal-support interaction and constructing surface oxygen defects [27,28]. Masanori et al [29] studied the use of La 2 O 3 -modified Ni/Al 2 O 3 catalysts for kerosene steam reforming and found that the activity, stability and hydrogen yield of the catalysts were increased.…”
Section: Introductionmentioning
confidence: 99%
“…There are various common strategies to improve catalyst stability, such as reducing the acidic sites of the support [26], enhancing metal-support interaction and constructing surface oxygen defects [27,28]. Masanori et al [29] studied the use of La 2 O 3 -modified Ni/Al 2 O 3 catalysts for kerosene steam reforming and found that the activity, stability and hydrogen yield of the catalysts were increased.…”
Section: Introductionmentioning
confidence: 99%
“…The types of catalysts that are used in the catalytic decomposition of methane processes are metallic and carbonaceous materials [18]. However, carbonaceous catalysts exhibit lower CH 4 consumption and reaction rates compared with metallic catalysts; hence, they are not employed frequently [19].…”
Section: Introductionmentioning
confidence: 99%